Cerebral Folate Deficiency & Receptor Mutations - J Gordon Millichap (Pediatric Neurology Briefs, 2012)
Researchers at University Medical Centre Gottingen, other centers in Germany, and Helsinki University Central Hospital, Finland screened 72 children with low 5-methyltetrahydrofolate (5-MTHF) concentrations in the CSF who developed neurological abnormalities after infancy.